Hubungan Pengetahuan Dan Sikap Wanita Usia Subur Dengan Minat Melakukan IVA Test Di Wilayah Kerja Puskesmas Mensiku Kecamatan Binjai Hulu Kabupaten Sintang Provinsi Kalimantan Barat Tahun 2024 - Khairunnisa Situmorang; Humaida Hanim; Mery Christie; Nia Habeahan (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Visual Inspection with Acetic Acid (VIA) is a simple, inexpensive, and effective method for cervical cancer screening. However, the interest of women of reproductive age (WRA) in undergoing VIA tests remains low. It is believed that knowledge and attitude significantly influence their interest in undergoing VIA screening. This study aims to analyze the relationship between knowledge and attitude of women of reproductive age and their interest in undergoing VIA tests in the working area of Mensiku Public Health Center, Binjai Hulu District, Sintang Regency, West Kalimantan Province, in 2024. The study employed a cross-sectional design with a quantitative approach, with a sample of WRA selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using chi-square statistical tests. The results showed a significant relationship between knowledge level, attitude, and the interest in undergoing VIA tests. Women with good knowledge and positive attitudes had a higher interest in undergoing VIA screening compared to those with poor knowledge and negative attitudes. Therefore, improving knowledge and fostering positive attitudes toward VIA tests are essential to increase the interest of WRA in undergoing this screening, which could serve as an initial step in preventing cervical cancer.